(3GdWGbI GdcgQheZfGWjSjIs - (3GdLhNj, YjSi eMeO jGSjfs ((3YeGf, GdCQOf (B:s (3ecJHI GdeLJeY GdYQHj,s, 2006)
(3deMI JGQjNjI Yf GdcgQheZfGWjSjI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdeZfGWjSjI GdcgQHGFjIs